Peningkatan mutu proses pembelajaran melalui pelatihan Pedagogik Content Knowledge (PCK) - Usman Mulbar; Alimuddin Alimuddin; Ilham Minggi; Ahmad Zaki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The PKM program focused on providing trainingand mentoring activities to participants regarding PedagogicContent Knowledge (PCK) to improve the quality of thelearning process with the aims of (1) to increase knowledgeabout PCK, (2) participants can implement the PCK well in thelearning process, and (3) participants can disseminateknowledge of PCK. The main target audience in this PKMProgram included school supervisors, school principal, andschool teachers in the Tinggimoncong District, GowaRegency, South-Sulawesi Province. The results obtained in theprogram showed that knowledge and concepts of PCK of theparticipants increased, development skills of PCK of theparticipants were increase, PKM program participants couldcreate examples and compile the PCK activities in learningclasses, and PKM program participants could implement thePCK in the learning process at school. Other results obtainedwere the increased motivation of participants in knowing thePCK and the high enthusiasm of participants in disseminatingthe results of the PKM program, especially the informationabout PCK.